2022
DOI: 10.3390/ijms23137000
|View full text |Cite
|
Sign up to set email alerts
|

Group II Metabotropic Glutamate Receptors Reduce Apoptosis and Regulate BDNF and GDNF Levels in Hypoxic-Ischemic Injury in Neonatal Rats

Abstract: Birth asphyxia causes brain injury in neonates, but a fully successful treatment has yet to be developed. This study aimed to investigate the effect of group II mGlu receptors activation after experimental birth asphyxia (hypoxia-ischemia) on the expression of factors involved in apoptosis and neuroprotective neurotrophins. Hypoxia-ischemia (HI) on 7-day-old rats was used as an experimental model. The effects of intraperitoneal application of mGluR2 agonist LY379268 (5 mg/kg) and the specific mGluR3 agonist NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Firstly, ischemia and hypoxia resulting from heart failure may lead to a decrease in BDNF levels. 68 Secondly, elevated miR-1 levels in the heart and blood of myocardial infarction may enter the brain through blood circulation, leading to a decrease in BDNF expression levels in the brain and ultimately leading to cognitive impairment. 69,70 Finally, both HF and CI share common pathological mechanisms, such as inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, ischemia and hypoxia resulting from heart failure may lead to a decrease in BDNF levels. 68 Secondly, elevated miR-1 levels in the heart and blood of myocardial infarction may enter the brain through blood circulation, leading to a decrease in BDNF expression levels in the brain and ultimately leading to cognitive impairment. 69,70 Finally, both HF and CI share common pathological mechanisms, such as inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…1 Multiple studies 31,32 have demonstrated altered BDNF levels following HI insults, with reported increases and decreases in various brain regions. Specifically, several of these studies 33,34 have proposed that HI insults induce neurobehavioral deficits by decreasing BDNF levels in the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Multiple studies 31 , 32 have demonstrated altered BDNF levels following HI insults, with reported increases and decreases in various brain regions. Specifically, several of these studies 33 , 34 have proposed that HI insults induce neurobehavioral deficits by decreasing BDNF levels in the developing brain. Consistent with these observations, the present study confirmed a rapid decrease in BDNF levels in the ipsilateral hippocampus following neonatal HIBD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a number of studies have shown that recombinant neurotrophic factors are highly effective in models of various pathologies, including cerebral ischemia and neurodegenerative diseases, both in vitro and in vivo [ 25 , 26 , 34 , 35 , 36 ]. However, many methodological difficulties, including overcoming the blood–brain barrier and the short period of active molecules’ degradation, call into question the potential use of BDNF and GDNF in clinical practice.…”
Section: Discussionmentioning
confidence: 99%